Bolstering environmental (in)justice claims with a quasi-experimental research design. (December 2015) - Funderburg, Richard; Laurian, Lucie
Highlights: Using a spatially explicit propensity score matching model, we statistically pair 99 twin French communes to 99 communes that opened a waste incinerator between 1968 and 2005, except that the twins never opened an incinerator. We conduct a before and after, matched control quasi-experiment on net migration and employment growth of incinerator towns and find weak evidence that incinerator location influences concentration of immigrants and no evidence of a migration impact on the established population. Conversely, a town with a one percent greater concentration of immigrants (foreign born or born abroad) is estimated to be 21–23 percent more likely to have opened a waste incinerator than towns with smaller immigrant populations and the effect persisted in 1968 and 1999. Incinerators have contributed to employment growth over a longer term for towns that opened them, but the effect is not permanent. Specifically incinerators increased employment 33 percent in communes that opened them compared to the counterfactual, a significant impact that disappears in the third census after the intervention. By 2008, incinerators in towns with many immigrants had more burners and 71 percent greater capacity and emitted 89 percent more carbon dioxide (CO2 ) than towns with low concentrations of immigrants. Abstract: Claims of environmental injustice are often confounded by the potential for reverse causality. An undesirable land use may concentrate minorities and poor people locally as the established population moves out and others remain or move in. This paper addresses the issue of causality for the case of waste incinerators in France with a before and after, matched control design. Site selection, population migration, and the capacity and emissions of incinerators have mutually reinforcing effects that can exacerbate environmental injustice. We develop a predictive model of incinerator siting in France and use it to identify a viable twin location for every incinerator site, similar in most aspects, except the twins were not selected to host a facility. In turn, these matches enable us to construct explicit counterfactuals and measure the true impact of incinerators on demographic change. We find solid evidence that concentration of immigrants influences incinerator location and weak evidence for the converse, that incinerator location influences concentration of immigrant populations. We also find that concentration of immigrants greatly affects the operations of incinerators, with greater capacity and greater emissions at incinerators located near the highest concentrations of immigrant populations.